Cardiometabolic Effects of a 12-Month, COVID-19 Lockdown-Interrupted Lifestyle Education Program for Arab Adolescents - Al-Daghri, Nasser M.; Wani, Kaiser; Khattak, Malak N. K.; Alnaami, Abdullah M.; Amer, Osama E.; Aljohani, Naji J.; Hameidi, Abdulaziz; Alfawaz, Hanan; Alharbi, Mohammed; Sabico, Shaun (Frontiers in Pediatrics, 2022)
Background: Childhood obesity and pediatric metabolic syndrome (MetS) have steadily increased during the last decade in Saudi Arabia. Intervention programs to prevent cardiometabolic disorders in Arab youth are needed. Objective: In this multi-school intervention study which was disrupted by Covid-19-imposed lockdowns (Sept 2019-April 2021), a 12-month lifestyle education program focused on improving the cardiometabolic status of Arab adolescents was investigated. Methods: A total of 2677 Saudi students aged 12-18 years were recruited from 60 different secondary and preparatory year schools in Riyadh city, Saudi Arabia. The intervention was initially in-person counseling sessions and the subsequent sessions conducted virtually post-pandemic. Baseline anthropometrics and fasting blood samples for glucose, HbA1c and lipid assessments were collected at baseline and after 12 months (704 participants). Results: Only 704 out of 2677 (73.7% dropout) completed the intervention. At baseline, 19.6% of the participants were overweight and 18.1% were obese. A modest but significant decrease in the prevalence of central obesity [11.2% versus 6.7% (-4.5% change, p=0.002)], hypertension [22.3% versus 11.4% (-10.9% change, p<0.001)] and low-HDL cholesterol [61.6% versus 23.3% (-38.3% change, p<0.001)] were noted. Consequently, the prevalence of hypertriglyceridemia increased from 22.7% to 56.3% (+33.6%, p<0.001) overtime. Also, the proportion of subjects who were able to change their status from MetS to non-MetS was significantly more in overweight/obese at baseline than normal weight (16.9% vs 3.6%, adjusted OR =3.42, p<0.001). Conclusions: Interrupted lifestyle education programs secondary to COVID-19 imposed lockdowns still provided modest effects in improving cardiometabolic indices of Arab adolescents. Given the high digital literacy of Arab youth, improving the delivery of virtual lifestyle education programs may prove beneficial.